Estrategias de enseñanza y logro de aprendizajes en la competencia escribe diversos tipos de textos en inglés en estudiantes del segundo grado de secundaria del Colegio San Agustín, Iquitos 2022 - Gonzales Pino, Lessy Smith (2022)
This section briefly presents what was done in the investigation. The general objective was to relate the teaching and learning achievement strategies in the competition write various types of texts in English in students of the second grade of secondary school of the Colegio San Agustin de Iquitos in the current year 2022. For this purpose, the type of relational research, through a bivariate, field, and cross-sectional design. The population studied was 85 second grade high school students, the sample being the same as the population for having adopted the census technique. To obtain the information, a written test was prepared and through a survey it was obtained, prior to this action an expert judgment was made on the instrument to be applied. It is concluded that the relationship between the use of teaching strategies and the achievement of learning in the competition writes various types of English texts is in 30 (35.3%) that present learning achievement at the beginning have a medium level of use of teaching strategies, in the 37 (42.5%) that have learning achievements in process show a medium level of use of teaching strategies and in the 18 (21.2%) of students with achieved learning achievement, the high level predominates in the use of teaching strategies.